2021
DOI: 10.3844/ojbsci.2021.120.135
|View full text |Cite
|
Sign up to set email alerts
|

A Meat-Derived Lactic Acid Bacteria, Lactobacillus plantarum IIA, Expresses a Functional Parvulin-Like Protein with Unique Structural Property

Abstract: The genome sequence of a Lactic Acid Bacterium (LAB) Lactobacillus plantarum IIA contains a single gene encoding a parvulin-like protein (Par-LpIIA). This protein belongs to Peptidyl Prolyl cis-trans Isomerase (PPIase) family proteins that catalyze a slow cis-trans isomerization of cis prolyl bond during protein folding. This study aims to provide molecular and biochemical evidences of the existence of Par-LpIIA in L. plantarum IIA and have an insight into its structural properties. The result showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…This capacity is presumably because this strain secreted some proteases which can hydrolyze proteins in the muscles. Budiman et al (2021) indicated that the genome sequence of this strain harbors some functional genes for foldases and proteases. One protease gene encodes a caseinolytic protease (Clp) which is known to be an essential protease involved in cell division, stress responses, and pathogenicity of bacteria (Frees et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This capacity is presumably because this strain secreted some proteases which can hydrolyze proteins in the muscles. Budiman et al (2021) indicated that the genome sequence of this strain harbors some functional genes for foldases and proteases. One protease gene encodes a caseinolytic protease (Clp) which is known to be an essential protease involved in cell division, stress responses, and pathogenicity of bacteria (Frees et al, 2014).…”
Section: Introductionmentioning
confidence: 99%